Analysis of the Application of Nursing Care Self Management Education (DSME) through Bedside Teaching in Meeting the Needs of Self-Actualization in Diabetes Mellitus Patients at Royal Prima Hospital Medan in 2026 - Mutiara Rolika Putri Sitompul; Kezia Chaterine Hasibuan; Nidia Felisia Halawa; Theresia; Julia Yosida Damanik; Basri (Universitas Muhammadiyah Palu, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease with an increasing prevalence and requires optimal self-management to prevent complications and improve the quality of life of patients. One approach that can be done is Diabetes Self Management Education (DSME) through bedside teaching to improve patients' ability to take care of themselves and meet their self-actualization needs. This study aims to analyze the application of DSME nursing care through bedside teaching in meeting the needs of self-actualization in Diabetes Mellitus patients at Royal Prima Hospital Medan in 2026. The method used was a case study with a nursing process approach including study, diagnosis, intervention, implementation, and evaluation of nursing for 3×24 hours in a patient Mrs. N aged 56 years with a medical diagnosis of Diabetes Mellitus. The results of the study showed that patients experienced instability in blood glucose levels with a KGD of 460 mg/dL, a deficit in knowledge related to the disease, and a risk of situationally low self-esteem due to insulin use. Interventions provided were in the form of hyperglycemic management, health education through DSME bedside teaching, and self-awareness promotion. After three days of nursing treatment, there was an improvement in the patient's condition which was characterized by a decrease in blood glucose levels to 150 mg/dL, an increase in the patient's knowledge about DM management, adherence to treatment, and an increase in the patient's confidence in accepting the use of insulin. The implementation of DSME through bedside teaching has been proven to help improve patients' self-management skills and support the fulfillment of self-actualization needs in Diabetes Mellitus patients.